Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors

Calculator Output

Simplifying
2x + 6 = 4x + -2

Reorder the terms:
6 + 2x = 4x + -2

Reorder the terms:
6 + 2x = -2 + 4x

Solving
6 + 2x = -2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6 + 2x + -4x = -2 + 4x + -4x

Combine like terms: 2x + -4x = -2x
6 + -2x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
6 + -2x = -2 + 0
6 + -2x = -2

Add '-6' to each side of the equation.
6 + -6 + -2x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = -2 + -6
-2x = -2 + -6

Combine like terms: -2 + -6 = -8
-2x = -8

Divide each side by '-2'.
x = 4

Simplifying
x = 4
Processing time: 0 ms. 51309185 equations since February 08, 2004.   Disclaimer

Equation Calculator & Solver

Equation: Variable:
       
Hint: Selecting "AUTO" in the variable box will make the calculator automatically solve for the first variable it sees.

Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors